Reflections on the Undergraduate Research Experience of Three Former NCAA Division I Athletes - Rubin, Lisa M.; Lombardi, Alyssa A.; Felice, Kennedy; Donato, Michael A. (My University, 2020)
Undergraduate research (UR) opportunities are important for college students to engage in areas of interest, gain valuable skills, and contribute to their learning outside of the classroom (Mahatmya et al., 2017). There have been a few studies on college athletes engaged in high impact practices (HIPs) like study abroad programs (Navarro et al., 2020), first-year seminars (Grafnetterova et al., 2020), and learning communities (Mamerow & Navarro, 2014). However, little has been studied on athletes’ engagement in UR (also a HIP). While athletes may not be a large percentage of an institution’s student population, they are more visible in the campus community. College athletes face time constraints, balancing two full-time roles of student and athlete, often with limited time remaining to devote to extracurricular activities (Ishaq & Bass, 2019; Rubin & Moses, 2017). They also endure negative stereotypes, seen as outsiders by the student body and faculty, isolating themselves from campus involvement (Rubin & Moses, 2017; Simons et al., 2020). These stereotypes include the idea of the “dumb jock,” in which athletes are incapable of handling collegelevel work and require additional support to pass classes (Simons et al., 2007). Many campuses offer academic support in facilities designated specifically for athletes, beyond the typically weekday work hours (Rubin & Moses, 2017). Besides attending classes on campus, athletes spend most of their time in athletic facilities for meals, workouts, tutoring, and practices. In classes, they are more likely to sit with other athletes who understand their schedule and lifestyle (Rubin & Moses, 2017). Their rigid schedules might prohibit them from exploring student organizations or UR. Because of this, engaging athletes in UR is not as easy or obvious for faculty as it may be with other students. Yet, Gaston-Gayles and Hu (2009) discovered that athletes who engage in educationally purposeful activities, including faculty interaction and collaborative learning, improve in cognitive and academic outcomes. Since athletes’ college experience may differ significantly from that of other students, it is important to learn from former athletes’ participation in UR.